Результаты мечения трески (Gadus morhua callarias L.) в восточной и центральной Балтике. - Kondratovich, E.Ya. (1980)
4807 cod individuals from the period of 1972-1977 were tagged in different Baltic Sea areas, mainly in the Gotland Deep region, during the spawning period. On the basis of data received the intensity of cod migrations in different directions, its distribution by regions depending on hydrological regime in the spawning period and during the feeding are discussed. The cod tagged in Klaipeda and South Gotland areas is stated to perform the most extensive migrations, and the cod tagged in Bornholm region performs the shortest ones. The data received are of great importance in defining the cod distribution by fishing zones. 4. ausgabe des sonderheftes über fischereiliche untersuchungen der DDR und der UDSSR in der Ostsee. 4. выпуск совместного сборника научных статей по вопросам рыбохозяйственных исследований ГДР и СССР в Балтийском море. Published